A Synthesis of Surface Water Quality in Awash Basin, Ethiopia - Assegide, Endaweke; Alamirew, Tena; Dile, Yihun T.; Bayabil, Haimanote; Tessema, Bezaye; Zeleke, Gete (Frontiers in Water, 2022)
Developing countries like Ethiopia are grabbling with rapid population growth, urbanization, agricultural intensification, and climate change which put intense pressure on the availability and quality of water resources. The water quality degradation is exacerbating due to increasing urbanization, and agricultural activities. The average annual fertilizer uses in Ethiopia increased from 132,522 metric tons (mt) in 1996 to 858,825 mt in 2015. Pesticide use also increases significantly by 3327.7 mt/y from 2006 to 4211.5 mt/y in 2010. The Awash river is one of the most affected rivers by intensified irrigation schemes, industrial, and urbanization pollution. The Awash River and its tributaries are used for domestic, irrigation, industrial, and recreational purposes. However, as per Canadian water quality indices for the drinking and irrigation water quality, the upper Awash basin scored 34.79, and 46.39, respectively, in the poor and marginal categories; whereas the middle/lower basin indicated 32.25 and 62.78 in poor and marginal ranges, respectively. Dissolved phosphorous in the headwater tributaries is about 0.51 mg/l which is beyond the threshold (0.15mg/l). The water quality impairment is severe in the upper Awash Basin where more than 90 % of Addis Ababa's industries discharge their waste into nearby waterways without treatment; about 30 % of the population lacks access to a liquid waste disposal and treatment facility; only 16 % of the population is connected to the sewage system, and 25 % of the total waste generated enters freshwater systems without treatment. Many studies on water quality are reviewed and many of them are inconclusive for a number of reasons. For example, no comprehensive water quality research, lack of detailed combined spatial and temporal water quality data, and analysis to show the overall picture of the basin are a few of them. Despite the existence of the policy and legal tools, enforcement is lacking. Improving the ecological health of rivers necessitates policy revision as well as increased knowledge and engagement among implementers.